2016
DOI: 10.1177/0894318416662931
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Writing for Publication

Abstract: Disseminating new scientific knowledge through publication is critical for any discipline, including nursing. The challenge for nurse faculty is preparing emerging nurses with the skills, enthusiasm, and disposition to fully assume professional roles as nurse scientists and scholars, including that of author. Exploring how students learn to write for publication and barriers to writing for publication, recommendations are offered for teaching-learning as a guide to faculty in planning programs, developing curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Writing for publication is a challenge for health practitioners working in clinical settings right across the health professions (Singh & Mayer, 2014;Wenke, Ward et al, 2017;Yancey, 2016). Barriers to publication reportedly include lack of time due to clinical demands and lack of academic writing skills, coupled with an inability to persist in the face of these barriers (Harvey et al, 2013;Mickan et al, 2017;Yancey, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Writing for publication is a challenge for health practitioners working in clinical settings right across the health professions (Singh & Mayer, 2014;Wenke, Ward et al, 2017;Yancey, 2016). Barriers to publication reportedly include lack of time due to clinical demands and lack of academic writing skills, coupled with an inability to persist in the face of these barriers (Harvey et al, 2013;Mickan et al, 2017;Yancey, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Writing for publication is a challenge for health practitioners working in clinical settings right across the health professions (Singh & Mayer, 2014;Wenke, Ward et al, 2017;Yancey, 2016). Barriers to publication reportedly include lack of time due to clinical demands and lack of academic writing skills, coupled with an inability to persist in the face of these barriers (Harvey et al, 2013;Mickan et al, 2017;Yancey, 2016). Strategies to increase publication rates have included writing retreats over 1 or 2 days (Bullion & Brower, 2017;Jackson, 2008), writing workshops (Kulage & Larson, 2016), writing mentors (Kennedy, 2017) and peer reviewers (Geithner & Pollastro, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The skill of writing a peer reviewed paper is highly specialized and challenging. It is also a challenge to teach this skill, yet it is essential to do so, as students are often required to engage with complex academic texts as well as write scientific reports [1][2][3]. Other cited reasons are: (i) increasing scientific literacy; (ii) staying informed of progress in a particular field of study; (iii) understanding the causation, clinical features, and natural history of a disease; (iv) evaluating the effectiveness of diagnostic tests and clinical therapies; and (v) determining whether there is support for or opposition to a particular argument [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the research exploring their current roles is limited. Nurses often encounter barriers in showing their roles, positions, ideas, strategies, and successes (Yancey, 2016). One review article (Corley et al, 2016) revealed a lack of literature on the role of nurses in all types of Neglected Tropical Diseases (NTDs).…”
Section: Introductionmentioning
confidence: 99%